High-Throughput Microbore LC-MS Lipidomics to Investigate APOE Phenotypes - Gadara, Darshak; Berka, Vratislav; Spacil, Zdenek (Analytical chemistry, 2024)
Microflow liquid chromatography interfaced with mass spectrometry (μLC-MS/MS) is increasingly applied for high-throughput profiling of biological samples and has been proven to have an acceptable trade-off between sensitivity and reproducibility. However, lipidomics applications are scarce. We optimized a μLC-MS/MS system utilizing a 1 mm inner diameter × 100 mm column coupled to a triple quadrupole mass spectrometer to establish a sensitive, high-throughput, and robust single-shot lipidomics workflow. Compared to conventional lipidomics methods, we achieve a ∼4-fold increase in response, facilitating quantification of 351 lipid species from a single iPSC-derived cerebral organoid during a 15 min LC-MS analysis. Consecutively, we injected 303 samples over ∼75 h to prove the robustness and reproducibility of the microflow separation. As a proof of concept, μLC-MS/MS analysis of Alzheimer's disease patient-derived iPSC cerebral organoid reveals differential lipid metabolism depending on APOE phenotype (E3/3 vs E4/4). Microflow separation proves to be an environmentally friendly and cost-effective method as it reduces the consumption of harmful solvents. Also, the data demonstrate robust, in-depth, high-throughput performance to enable routine clinical or biomedical applications.
Keywords: Humans; chromatografie kapalinová; Tandem Mass Spectrometry; reprodukovatelnost výsledků; apolipoproteiny E; Apolipoproteins E; lipidomika; Reproducibility of Results; Liquid Chromatography-Mass Spectrometry; tandemová hmotnostní spektrometrie; Lipidomics; Chromatography, Liquid; kapalinová chromatografie-hmotnostní spektrometrie; Phenotype; fenotyp; lidé